Pengaruh Pendekatan Konstruktivisme terhadap Hasil Belajar pada Subtema 2 Kebersamaan dalam Keberagaman Kelas IV SD Negeri Sinaksak - Sanitia; Lisbet N. Sihombing; Hetdy Sitio (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
This study aims to improve student learning outcomes in thematic learning on sub-theme 2 Togetherness in Diversity. The research used is quantitative research because the problems that are brought are clearly related to research data in the form of facts that are proven through numbers and facts that occur in the field through observation and analysis using statistics. The population is 40 students. The sample is 40 students. The variables in this study are the Constructivism Approach (X) and learning outcomes (Y). Methods of collecting data with tests. The results of this study indicate that there is success in the constructivist approach to student learning outcomes in thematic subjects at SD Negeri Sinaksak. This success is proven by an increase in the value in learning activities with a significant difference in learning outcomes where the experimental class has an increase of 68.35% and the control class has 57.15%, it can be concluded that the constructivism approach to student learning outcomes in sub-theme 2 togetherness In the diversity of class IV, SD Negeri Sinaksak is said to be quite effective, on the contrary, the control class that uses the conventional approach is said to be less effective